The Influence of Financial Literacy and Shopping Habits on The Financial Management of Economic Education Students - Wuisang, Jerry Rommy Herter; Rooroh, Agnes; Christian, William (AIBPM Publisher, 2023)
The goal of this study is to determine how financial literacy and buying habits impact the money management of economics students at Manado State University. This study used a quantitative methodology using SPSS 25 as assistance. 175 students who were enrolled in economic education programs at Manado State University for the 2019 and 2020 academic years made up the population of this study, and the sample size was 64 respondents. The Slovin technique, which has a 10% error rate, yielded 64 responders, and the number of samples was determined by simple random sampling. Multiple linear regression analysis, the Test t and Test f hypothesis tests, and the distribution of questionnaires as a data collecting method were all used to assess the results. It is known that the sig value for X1's partial effect on Y is 0.676 > 0.05. The calculated t value is 0.420 from the 1999 T table. The sig value of the partial effect of X2 on Y is 0.002 0.05. And the 1999 t table has a t count value of 3259. A sig value of 0.005 0.05 indicates that X 1 and X 2 have an influence on Y simultaneously.